2013
DOI: 10.1007/s10661-013-3401-2
|View full text |Cite|
|
Sign up to set email alerts
|

CDOM fluorescence as a proxy of DOC concentration in natural waters: a comparison of four contrasting tropical systems

Abstract: Chromophoric dissolved organic matter (CDOM) fluorescence or absorption is often proposed as a rapid alternative to chemical methods for the estimation of bulk dissolved organic carbon (DOC) concentration in natural waters. However, the robustness of this method across a wide range of systems remains to be shown. We measured CDOM fluorescence and DOC concentration in four tropical freshwater and coastal environments (estuary and coastal, tropical shallow lakes, water from the freshwater lens of two small islan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Therefore, a strong relationship between CDOM and DOC may not exist for the open ocean, dominated by marine autochtonously produced CDOM [cf. Siegel et al, 2002;Rochelle-Newall et al, 2014]. In contrast, in areas strongly influenced by inputs of terrestrial dissolved organic matter, significant positive relationships have been found between CDOM and DOC [e.g., Spencer et al, 2009;Fichot and Benner, 2012].…”
Section: Properties and Origin Of Cdom During Experimentsmentioning
confidence: 99%
“…Therefore, a strong relationship between CDOM and DOC may not exist for the open ocean, dominated by marine autochtonously produced CDOM [cf. Siegel et al, 2002;Rochelle-Newall et al, 2014]. In contrast, in areas strongly influenced by inputs of terrestrial dissolved organic matter, significant positive relationships have been found between CDOM and DOC [e.g., Spencer et al, 2009;Fichot and Benner, 2012].…”
Section: Properties and Origin Of Cdom During Experimentsmentioning
confidence: 99%
“…Substances that are excited in the UV spectral range, but emit in the visible spectral range were identified as fulvic-and humic-like FDOM components [Coble, 1996;Gu eguen and Kowalczuk, 2013] and have been related to semirefractory or refractory DOM [Coble, 1996].Optically active DOM may be used for carbon assessment in aquatic systems, where DOM cycling is controlled by conservative mixing. Thus, CDOM absorption has been used to estimate DOC concentrations in field studies [Fichot and Benner, 2012;Rochelle-Newall et al, 2014]. In remote sensing techniques, light attenuation is used by satellites to derive CDOM signal, and, by assuming a direct relationship between CDOM absorption and DOC concentrations, the distribution of DOC in surface waters [Del Castillo, 2007].…”
mentioning
confidence: 99%
“…Around the timing of the phytoplankton bloom, as reported around DoY 123.5 (Fig 4) from MODIS-derived Chlorophyll-a values, our ADCP SPM data showed wisps of high backscatter in the upper water layers (up to a water depth of -20 m; 10 m above seabed). Other possible causes for this shallow backscatter anomaly were excluded: wave heights were around 0.5 m only, and the nearest ships were more than 4 km away; values for colour dissolved organic matter, as measured by the Wave Glider, and a useful proxy for debris from dead organic matter [60] were low too.…”
Section: Discussionmentioning
confidence: 99%